Comparative Study of Gradient Gravity Method Between Signal Processing and Direct Measurement. Issue 1 (1st May 2022) - Nugraha, Purwaditya; Kadir, Wawan Gunawan A.; Setianingsih,
Abstract: The vertical gradient gravity method is one of the developments from the conventional gravity method. The advantage of this method is that it is able to detect the presence of shallow anomalies below the soil surface. In addition, this method is also able to minimize errors resulting from processing and correcting data. This research was conducted by testing the vertical gradient gravity method which is carried out with signal processing or with a vertical gradient gravity filter and the vertical gradient gravity method which is carried out by direct measurement. It was found that the vertical gradient gravity method which was carried out by direct measurements resulted in a clearer pattern in determining the presence of shallow anomaly sources.